Consumer Protection in the Fintech Peer-to-Peer Lending Ecosystem in Indonesia Based on the Principles of Justice and Legal Certainty - Mohd Ikrom Yuserma; Umar Hasan; Indriya Fathni (CV. Rayyan Dwi Bharata, 2026)
This study aims to analyze the regulation of consumer protection within the fintech peer-to-peer lending ecosystem in Indonesia based on the principles of justice and legal certainty. The results of the analysis indicate that: First, the regulation of fintech peer-to-peer lending services in Indonesia is governed by Law Number 8 of 1999 concerning Consumer Protection and the Financial Services Authority Regulation Number 10/POJK.05/2022 on Technology-Based Collective Funding Services. These regulations provide a legal framework that guarantees consumer rights, including the right to security, comfort, and safety in transactions, as well as the obligation of providers to maintain data confidentiality, provide complaint mechanisms, and conduct business activities transparently and responsibly. However, the existing regulations are still general and partially implicit, which in practice poses challenges regarding the certainty of providers’ responsibility for consumer losses, particularly in terms of direct compensation. Second, consumer protection in the implementation of fintech peer-to-peer lending must be based on the principles of justice, balance, and legal certainty. These principles require equality of rights and obligations between providers and consumers, transparency of information, accountability, and effective dispute resolution mechanisms. Although supervisory mechanisms and administrative sanctions by the Financial Services Authority (OJK) have been established, legal certainty for consumers regarding compensation for losses still requires more explicit and specific regulations to avoid ambiguities. Clearer regulations would provide consumers with more effective legal protection, while encouraging providers to improve service quality and transaction security, thereby creating a fair, transparent, and trustworthy fintech ecosystem in Indonesia. Furthermore, existing regulations do not yet strengthen the obligation of providers to create written agreements electronically for all parties involved in transactions, leaving the rights and obligations of each party unclear and potentially resulting in the loss of provider accountability. Strengthening electronic written agreements aims to ensure comprehensive consumer protection and prevent potential disputes in the future.